Biology and the Statistic Demographic of Aphis glycines Matsumura (Hemiptera: Aphididae) on the Soybean with Plant Growth Promoting Rhizobacteria (PGPR) Treatment - Hermanu Triwidodo; Anggun Agustini; Listihani Listihani (Universitas Gadjah Mada, 2020)
A correction has been published:Erratum to “Biology and the Statistic Demographic of Aphis glycines Matsumura (Hemiptera: Aphididae) on the Soybean with Plant Growth Promoting Rhizobacteria (PGPR) Treatment” [Jurnal Perlindungan Tanaman Indonesia, 24(1), 54 ̶ 60]Plant Growth Promoting Rhizobacteria (PGPR) applied to different plants may suppress pests population developments. This research was to study the capability of a commercial PGPR product contained Bacillus polymyxa and Pseudomonas fluorescens in suppressing population developments of Aphis glycines Matsumura (Hemiptera: Aphididae). The biology and demographic statistics of A. glycines reared on soybean with and without the PGPR applications were compared. The PGPR suspensions of 5 g formulation per liter water were used to soak soybean seed for 15 minutes and to water soybean plant 2 weeks after transplanting. Cohorts of 65 first instar A. glycines of each treatment were observed daily and individual mortality, molting, and fecundity were recorded until the last individual dead. Second instar stadium of A. glycines reared on treated plant lasted longer than those reared on untreated plant, i.e. 1.4 and 1.1 days, respectively. These resulted on a longer life cycle for A. glycines reared on treated plant than on untreated plant, i.e. 4.9 and 4.5 days, respectively. In turn, it caused the A. glycines population to experienceslower growth on treated plants than on untreated plants. The values of A. glycines GRR, Ro, rm, T and DT on treated plants were 71.834, 57.780, 0.557, 7.287 and 1.245, consecutively; whilst that of untreated plants were 104.861, 63.326, 0.586, 7.084 and 1.184, respectively.